Adaptive Reuse of Mega-Stores: Transforming an Icon of Suburban Inefficiency into a Model of Sustainability. - Hoffman, Elaine G. (Tufts Archival Research Center, 2005)
As the main focus of this thesis, I analyze the practice of converting these mega-stores from big abandoned boxes to workable sites, and compare this technique to other alternatives, such as destruction of the building and its surrounding parking lot. Through examining five case studies, I explore how the re-adaptation and the reuse of big box stores address the problems that they inherently pose. Through this analysis, I assess the environmental benefits and potential harms of the re-adaptation of mega-stores.